Coaly and lacustrine hydrocarbon source rocks in Permo-Carboniferous graben deposits (Weiach well, Northern Switzerland). (April 2023) - Ajuaba, Stephen; Sachsenhofer, Reinhard F.; Meier, Verena; Gross, Doris; Schnyder, Johann; Omodeo-Salé, Silvia; Moscariello, Andrea; Misch, David
Abstract: Permo-Carboniferous graben sediments in the North Alpine Foreland Basin (NAFB) include Upper Carboniferous (Stephanian) coal-measures and lower Permian (lower Autunian) lacustrine shales with high organic matter contents. Coals are probably the source for a gas accumulation in Switzerland, while the bituminous shales are potential source rocks for oil. In order to study the hydrocarbon potential of coal and bituminous shales and to contribute to the understanding of their depositional environment, 90 core samples from the Weiach-1 well (northern Switzerland) were investigated using organic petrographic, palynofacies, Rock-Eval pyrolysis, and geochemical techniques (incl. biomarker analysis and compound-specific carbon isotopy). Carboniferous coal seams are up to 10 m thick and were deposited in low-lying freshwater mires. They contain a significant gas potential and reached a maturity stage related to the onset of gas generation. Sapropelic rocks were not observed in the coal-bearing succession. Organic matter-rich Permian shales (Autunian shales) were deposited in anoxic lakes with a stratified water column. The organic matter is of mixed aquatic and terrigenous origin. δ 13 C values of chlorophyll-derived isoprenoids provide evidence for reworking of organic matter in the water column. The Autunian shales have a strongly varying, but locally very good oil potential. They reached early oil window maturity, but did not yet generate significant amounts of hydrocarbons. The main shale interval in the studied borehole is about 12 m thick and will generate about 0.35 tHC/m 2 when mature. A comparison with literature data shows that it is possible to distinguish oils generated from Permian, Jurassic and Oligocene source rocks based on biomarker ratios and isotope data. Highlights: Gas-prone Carboniferous coals in the Constance-Frick trough were deposited in low-lying freshwater mires.. Permian lacustrine shales deposited in anoxic lakes with a stratified water column contain high amounts of Type II kerogen. Permian shales can generate considerable amounts of liquid hydrocarbons. Oil from Permian shales can be distinguished from oil with younger source rocks using biomarker and isotope ratios.